Sovereign Ceilings ""Lite""? The Impact of Sovereign Ratingson Corporate Ratings in Emerging Market Economies - Borensztein, Eduardo (International Monetary Fund, 2007)
Although credit rating agencies have gradually moved away from a policy of never rating a private borrower above the sovereign (the ""sovereign ceiling"") it appears that sovereign ratings remain a significant determinant of the credit rating assigned to corporations. We examine this link using data for advanced and emerging economies over the past decade and conclude that the sovereign ratings have a significant and robust effect on private ratings even after controlling for country specific macroeconomic conditions and firm-level performance indicators. This suggests that public debt management affects the private sector through a channel that had not been previously recognized